Studies on the Occurrence of Selected Heavy Metals in Periyar Industrial River Belt With Emphasis Onpotassium DichromateToxicity in ANAbAS Testudineus. - Liya V. Benjamin (Dept .of Aquatic Environment Mangement, 2017)
Abstract- Availability and concentration of five heavy metals (Cr, Cd, Cu, Pb, Zn) in water and sediment of the Periyar Industrial river belt were studied during post monsoon and pre-monsoon periods, using Inductively Coupled Plasma-Optical Emission Spectroscopy (ICPOES). Spatial and temporal variation of physico-chemical parameters and their correlation with heavy metal concentration were also analysed. The accumulation of heavy metal was relatively high in sediment compared to water. The mean residue level of heavy metals in the sediment (mg/Kg) were in order of Zinc > Lead> Chromium >Copper > Cadmium. While comparing the values against the standards proposed under US National Oceanic and Atmospheric Administration (NOAA) guidelines, it was seen that sediments samples from stations near to the industrial area, were beyond the permissible level. Results clearly indicate that higher levels of heavy metals in sediment could have adverse biological impacts. The results observed in the present study are comparable to the earlier reports as well as the last five years data published by the Pollution Control Board. As a follow-up the study on the effect of sub lethal concentrations of Potassium dicromate on freshwater fish, Anabas testudineus was envisaged to understand its toxicity through hematological and histopathological tools. The LC50 value at 96 hr for this metal was found to be 58 mg/L in Anabas testudineus. The data obtained were statistically evaluated using Finney’s probit analysis method. The fishes were exposed to two sublethal concentrations before assessing their effect through haematology and histology. Histological preparations of liver, gill and kidney tissues were randomly examined for histopathological lesions. Results of the histological examinations showed abnormalities in liver tissue such as degeneration of hepatocytes, dilation of sinusoids and necrosis in some area. Extensive hemorrhage was observed in gill and kidney tissue. Among the various haematological parameters evaluated the haematocrit value and RBC count were significantly reduced after 15days of exposure to the two sub lethal concentrations of potassium dichromate while the leucocyte count was significantly increased. Results emerging from the present study clearly indicate that the Periyar Industrial river belt has a considerable deposition of heavy metal in the sediment, which once perturbed has the potential to get released in the overlying water column. Once these heavy metals become bioavailable to the aquatic fauna it can cause severe physiological and biological alterations in these organisms including fishes. Hence a detailed study on the speciation of different heavy metal, their possible impact on biota and methods for its mitigation in deeply warranted.